2017
DOI: 10.7205/milmed-d-17-00003
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Complicated Grief in a Military Mental Health Clinic

Abstract: The findings from this preliminary investigation suggest that many service members receiving care in military mental health care are experiencing grief-related symptoms and distress, and a brief screen for grief can help capture many of those with grief related impairment. Research shows that CG needs to be directly targeted to treat its symptoms and associated impairment. We recommend that military mental health clinics consider adding some type of grief screener to their standard intake as well as making pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…CG comorbidity with PTSD may be especially relevant for military personnel, given the high risk for exposure to traumatic events as well as significant, sudden, and violent losses (e.g., Wisco et al, 2014;Toblin et al, 2012). A recent study in a military mental health clinic found 43.5% of outpatients were impacted by a significant loss, nearly half (46.1%) of whom exhibited clinically significant CG symptoms (Delaney et al, 2017). Losses during deployment, especially the loss of a fellow service member (FSM), were associated with greater CG symptom severity than other types of losses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CG comorbidity with PTSD may be especially relevant for military personnel, given the high risk for exposure to traumatic events as well as significant, sudden, and violent losses (e.g., Wisco et al, 2014;Toblin et al, 2012). A recent study in a military mental health clinic found 43.5% of outpatients were impacted by a significant loss, nearly half (46.1%) of whom exhibited clinically significant CG symptoms (Delaney et al, 2017). Losses during deployment, especially the loss of a fellow service member (FSM), were associated with greater CG symptom severity than other types of losses.…”
mentioning
confidence: 99%
“…This includes a study demonstrating an 8-fold risk of high suicidal ideation and behaviors even after controlling for depression and PTSD (Latham & Prigerson, 2004). Given the high prevalence and burden of comorbid CG and PTSD, screening for loss and CG is recommended in military mental health settings, but is not yet routinely implemented (Delaney et al, 2017). This could be, in part, due to our limited understanding of the impact of CG on PTSD outcomes.…”
mentioning
confidence: 99%
“…Most findings indicate that losing a child or partner is positively associated with PGD compared to the loss of other relatives (e.g., parents, siblings) or friends ( 14 , 15 , 21 , 33 , 34 ). Another loss-related variable is time since loss , for which some studies found no association ( 24 , 26 , 35 ), whilst others found an association with PGD ( 15 , 16 , 23 , 27 ). For instance, Newson et al found more time since loss to be associated with PGD ( 15 ), whereas Schaal et al found less time since loss to be associated with more grief ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…This screening tool utilizes five questions with three-point Lickert scale answers to assess for the extent of complications experienced in an individual’s grief experience. The BGQ has more recently been used to follow the course of grief reactions in military mental health ( Delaney et al, 2017 ) and grief (unspecified losses) presented in an integrated primary/behavioral health care clinic ( Patel et al, 2019 ). The screening method has been found to be a useful assessment tool assisting health providers to recognize grief and, if appropriate, refer a patient with prolonged grief symptoms for mental health services.…”
Section: Discussionmentioning
confidence: 99%